2015
DOI: 10.1002/ejoc.201500680
|View full text |Cite
|
Sign up to set email alerts
|

Hydroarylation of Alkynes with Phenols in the Presence of Gallium Complexes of a Labile N‐Ligand: Synthesis of Chromenes

Abstract: In the presence of (dpp‐bian)Ga–Ga(dpp‐bian) (1) and [dpp‐bian(Ph)C=C(H)]Ga–Ga[(H)C=C(Ph)dpp‐bian] (2) {dpp‐bian = 1,2‐bis[(2,6‐diisopropylphenyl)imino]acenaphthene}, phenylacetylene reacts with 1‐naphthol to give 2‐(1‐phenylvinyl)naphthalen‐1‐ol (3). In solution in the presence of complexes 1 or 2, compound 3 undergoes further dimerization to give 2‐[4‐methyl‐2,4‐diphenyl‐3,4‐dihydro‐2H‐benzo[h]chromen‐2‐yl]naphthalen‐1‐ol (C36H28O2), whose diastereomers 4 and 5 were isolated in crystalline form. Diastereomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The formation of chromene derivatives by alkenylation of phenol is consistent with the recent report by the Fedushkin group that appeared during the preparation of this manuscript. 9 Based on literature reports and our previous results, it is believed that the reaction proceeds through alkenylation of phenol to give (1-arylvinyl)phenol 3, which further undergoes second alkenylation and cycloisomerization to give indene in the case of 4-methoxyphenol. It is believed that due to the blocked C-3 position in the alkenylated product from 3-methoxyphenol, second alkenylation may be occurring at the vinylic position, and further cyclization leads to the formation of 5.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The formation of chromene derivatives by alkenylation of phenol is consistent with the recent report by the Fedushkin group that appeared during the preparation of this manuscript. 9 Based on literature reports and our previous results, it is believed that the reaction proceeds through alkenylation of phenol to give (1-arylvinyl)phenol 3, which further undergoes second alkenylation and cycloisomerization to give indene in the case of 4-methoxyphenol. It is believed that due to the blocked C-3 position in the alkenylated product from 3-methoxyphenol, second alkenylation may be occurring at the vinylic position, and further cyclization leads to the formation of 5.…”
Section: Resultsmentioning
confidence: 95%
“…[1][2][3][4] In particular, alkenylation of phenols with alkynes has been reported using SnCl 4 , 5 GaCl 3 , 6 nanoporous FeAl-KIT-5, 7 Pd 2 (dba) 3 8 and gallium complexes of labile N-ligands. 9 We have previously demonstrated that indium triflate [In(OTf ) 3 ] is an efficient catalyst for alkenylation of phenols using alkynes under microwave irradiation and the generated ortho-vinyl at phenols can be used for the synthesis of 1,2-diarylnaphtho[2,1-b]furans. 10 Indene ring frameworks are present in many natural products and bioactive pharmaceutical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, since no formation of cycloadducts of 62 with carbodiimides was observed, no clear evidence for GaLC was provided . The hydroarylation of phenylacetylene with 2‐naphthol also proceeded in the presence of catalytic amounts of 62 (Figure e) , . Phenols or internal alkynes were not suitable for this procedure and did not yield the desired compounds.…”
Section: Group 13 Element‐ligand Cooperativitymentioning
confidence: 99%
“…BIAN dipp , 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene, is a redox-active diimine ligand possessing the conformational rigidity of the diimine moiety and pronounced steric hindrances around nitrogen atoms. The unique reactivity of the main-group metal complexes with BIAN dipp ligand was shown by Fedushkin et al in the examples of addition (in some cases, reversible) and activation of substituted alkynes, alkenes [ 33 , 34 , 35 , 36 , 37 , 38 ]. It would be very interesting to combine sterically hindered NacNac ligands with redox-active sterically hindered o-iminobenzoquinones and bis-iminoacenaphthenes in a coordination sphere of rare earth.…”
Section: Introductionmentioning
confidence: 99%